Bipolar disorder - analysis of the impact of selected factors on treatment and course - review - Janicka, Ewelina Justyna; Rosińska, Kamila; Skibicka, Julia Natalia; Niedźwiedzka, Monika; Rosiński, Mateusz (Quality in Sport, 2024)
Introduction: Bipolar Disorder (BD) affects millions worldwide, impacting emotional, social, and cognitive functioning. This disorder, characterized by alternating episodes of mania and depression, carries high risks including suicide. Pharmacological treatment is the cornerstone of management, but its effectiveness can be limited, prompting the exploration of adjunctive treatment methods. This paper discusses the potential of interventions such as physical activity, sleep regulation, psychotherapy, and research on inflammation and gut microbiota as supplementary elements to standard BD treatment. Objective: This review aims to evaluate the role of adjunctive therapies, including physical activity, sleep regulation, inflammation, gut microbiota interventions, and psychotherapy, in improving outcomes for patients with BD. Materials and Methods: A literature review covering research on various forms of treatment for bipolar disorder, the impact of physical activity, inflammation, microbiota, sleep and psychotherapy in the treatment of this disease, published on the PubMed and Google Scholar platforms. Conclusions: Emerging evidence suggests that non-pharmacological interventions can complement standard treatments for BD. Physical activity helps alleviate depressive symptoms and improve psychosocial functioning, while regulating sleep patterns can reduce mood disturbances and suicidality. Managing systemic inflammation and optimizing gut microbiota may address neuropsychiatric symptoms and enhance cognitive performance. Psychotherapeutic approaches like CBT and MBCT lower relapse rates and improve quality of life. Integrating these strategies into routine care could enhance long-term management of BD.